73 MATERNAL DEPRESSION AND PRENATAL EXPOSURE TO METHAMPHETAMINE: PRELIMINARY NEONATAL NEURODEVELOPMENTAL FINDINGS FROM THE INFANT DEVELOPMENT, ENVIRONMENT, AND LIFESTYLE (IDEAL) STUDY. (1st January 2006) - Paz, M. S.; Smith, L. M.; LaGasse, L. L.; Derauf, C.; Grant, P.; Shah, R.; Arria, A.; Huestis, M.; Haning, W.; Strauss, A.; Grotta, Della S.; Fallone, M.; et al.
Abstract : Background: Maternal depression is associated with a higher incidence of behavioral problems in infants 3 months and older. The effects of maternal depression on neurodevelopment as early as 1 month of age have not been well characterized. Objective: To determine the effects of maternal depression on neonates exposed and not exposed to methamphetamine (MA) using the NICU Network Neurobehavioral Scale (NNNS). Design: The purpose of the IDEAL study is to determine the effects of prenatal MA exposure on child outcome. IDEAL screened 13, 808 subjects and 1, 632 were eligible and consented. 136 biological mother-infant dyads enrolled at four sites (Tulsa, OK, Des Moines, IA, Los Angeles, CA, and Honolulu, HI). MA subjects ( n = 50) were identified by self-report or GC/MS confirmation of amphetamine and metabolites in infant meconium. Comparison subjects ( n = 86) were matched (race, birth weight, maternal education, type of insurance), denied amphetamine use, and had a negative meconium screen. Both groups included prenatal alcohol, tobacco and marijuana use, but excluded use of opiates, LSD, PCP, or cocaine only. The NNNS, Beck Depression Inventory-II, and Brief Symptom Inventory were administered at the 1-month visit. General linear models tested the effects of maternal depression and prenatal MA exposure on NNNS, with and without covariates (prenatal alcohol, tobacco, marijuana, and cocaine exposure, SES, maternal weight gain, and 1-minute Apgar). Significance was accepted at p < .05. Results: Regardless of exposure status, maternal depression was associated with lower handling scores (p = .035), hypotonicity (p = .043), and elevated physiological stress (p = .041). No additional differences in NNNS scores were observed in neonates whose mothers were depressed and used MA during pregnancy. Conclusions: Maternal depression is associated with neurodevelopmental patterns of decreased arousal and increased stress. Prenatal MA exposure combined with maternal depression was not associated with any additional neurodevelopmental differences. These findings suggest that maternal depression can influence neurodevelopment in infants as early as 1 month of age.